The Influence of Organizational Culture Transformational Leadership Style on Employee Performance with Organizational Commitment as a Mediation Variable - Jaya, Umban Adi; Priyana, Indarta; Wulandari, Dwiwahjuni; Herlina, Elin; Albar, Fauzan Manafi (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2024)
In the era of globalization and increasingly tight business competition, employee performance is the key to company success. A positive organizational culture and transformational leadership style can influence employee motivation, productivity and commitment, which in turn improves organizational performance. This research investigates the influence of organizational culture and transformational leadership style on employee performance with organizational commitment as a mediating variable. Quantitative research methods were carried out on 100 employees at PT. Pratama Abadi Industri JX. The results of path analysis show that organizational culture and transformational leadership style have a significant effect on employee performance, with organizational commitment as a mediator. This research contributes to the development of human resource management theory and practice by highlighting the importance of organizational culture and leadership style in improving employee performance.